Mitochondrial apoptosis-related gene polymorphisms are associated with responses to anthracycline-based chemotherapy in acute myeloid leukaemia - Meng, Guangqiang; Li, Mingying; Xia, Yuan; Wu, Yuyan; Ma, Yuechan; Ji, Min; Zhang, Jingru; Ye, Jingjing; Sun, Tao; Ji, Chunyan (Frontiers in Oncology, 2023)
Background: Although anthracyclines are the first-line chemotherapy drugs for treating non-M3 acute myeloid leukaemia (AML), their efficacy remains poor. It is important to identify factors that influence the efficacy of anthracyclines against AML. Mitochondrial apoptosis-related genes play important roles in the pathogenesis, treatment, and prognosis of AML. Methods: We used the CRISPR/Cas9 screening system to find AML anthracyclines resistance related genes and some mitochondrial apoptosis-related genes, such as BCL2L11, CASP8, TP63, TP53BP2, PLAUR, SOD2, BNIP3L, and MMP9, were screened out. Then, DNA from 279 patients with AML and 321 healthy individuals were extracted and the contributions of single nucleotide polymorphisms of these genes to the patient’s chemotherapy response, susceptibility to AML, and overall survival were investigated. Results: The results showed that SNP rs4251864 in the PLAUR gene was associated with an increase in complete remission after anthracycline-based induction chemotherapy. rs4880 in SOD2 was associated with the response to the second course of chemotherapy, whereas rs3789068 in BCL2L11 was associated with susceptibility to AML. Conclusions: Our results about the association of SNPs in mitochondrial apoptosis-related genes with the response to anthracycline-based chemotherapy in AML provide an important reference for predicting the treatment outcomes in patients with this disease.